University Staff Insights on Interprofessional Education and Student-Led Clinic Opportunities at an Australian University - Collis JM; Barradell S; Broman P; Brownie S (Journal of Multidisciplinary Healthcare, 2024)
Julie M Collis,1 Sarah Barradell,1 Patrick Broman,1,2 Sharon Brownie1– 3 1School of Health Sciences, Swinburne University of Technology, Melbourne, VIC, Australia; 2Centre for Health and Social Practice, Waikato Institute of Technology, Hamilton, New Zealand; 3Griffith Health, Griffith University, Gold Coast, QLD, AustraliaCorrespondence: Julie M Collis, Email jcollis@swin.edu.auPurpose: Organizational and university staff buy-in and advocacy are critical considerations in planning successful interprofessional education (IPE) initiatives in healthcare, such as interprofessional student-led clinics (SLCs). This study was designed with the purpose of gaining deeper insight into current views and perspectives of academic and professional staff at an Australian university, as a precursor to planning IPE and SLC activities.Methods: All academic and professional staff from within the School of Health Sciences were invited to participate in the study. In-depth-qualitative interviews were conducted with 16 staff to explore academic and professional staff perspectives on IPE and SLCs. Reflexive thematic analysis was used to analyse the data.Results: Findings are grouped within five themes that incorporate broad perspectives on the tensions and possibilities of IPE and establishment of SLCs: Academic and professional staff commitment; Better/smarter IPE; Student-led clinic potential; Vision and innovation; and Strategy and resourcing. The themes reflect the high value placed on IPE by academic and professional staff and incorporate innovative ideas on how to prepare students for a rapidly changing and evolving healthcare environment. A reticence towards standard models of university based SLCs was expressed.Conclusion: Academic and professional staff insights suggest university leaders need to develop a greater strategic focus on improving IPE. Effective engagement with staff is required to support IPE planning and implementation. If considering implementation of SLCs, contemporary fit-for-purpose models should be explored such as partnerships with primary healthcare providers, community wellness facilities, and hospital clinics rather than traditional university-based clinics.Keywords: health occupations, interprofessional education, interdisciplinary placement, patient care team